Association between baseline radiographic damage and improvement in physical function after treatment of patients with rheumatoid arthritis. Issue 1 (29th July 2004) - Breedveld, F C; Han, C; Bala, M; van der Heijde, D; Baker, D; Kavanaugh, A F; Maini, R N; Lipsky, P E
Abstract : Objectives: To identify factors associated with poor physical function in rheumatoid arthritis and to assess whether baseline joint damage has an impact on improvement in physical function during infliximab treatment. Methods: 428 patients with active rheumatoid arthritis despite methotrexate treatment received methotrexate alone or with infliximab (3 mg/kg or 10 mg/kg every four or eight weeks) for 54 weeks (the ATTRACT trial). Data on clinical outcomes and physical function (assessed by the health assessment questionnaire (HAQ)) were collected. Structural damage was assessed using the van der Heijde modification of the Sharp score. Odds ratios (OR) for factors associated with severe functional disability (HAQ ⩾2.0) at baseline were estimated using multiple logistic regression analyses, and baseline factors related to the change in physical function after treatment at week 54 were determined. Results: Baseline radiographic scores were correlated with baseline HAQ scores. After adjustment for demographic characteristics in the logistic regression model, baseline disease activity scores, radiological joint damage, fatigue, and morning stiffness were found to be associated with severe functional disability (HAQ >2.0), with OR values of 2.00 (1.53 to 2.63), 1.82 (1.15 to 2.87), 1.19 (1.05 to 1.34), and 1.07 (1.01 to 1.13), respectively. In multiple linear regression analysis, physical disability, joint damage, and fatigue at baseline were correlated with less improvement in physical function after treatment. Infliximab treatment was associated with greater improvement in physical function. Conclusions: Greater joint damage at baseline was associated with poorer physical function at baseline and less improvement in physical function after treatment, underlining the importance of early intervention to slow the progression of joint destruction.